Method for preparing nanometer copper / si c composite antibacterial material with three-dimensional pore structure by confined freezing

CN122997122APending Publication Date: 2026-10-30BEIFANG UNIV OF NATITIES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611168639.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0023]本发明借助冷冻干燥工艺制备多孔陶瓷,所得样品孔隙尺寸规整,比表面积较高。该制备工艺环境友好,制备全过程无有害物质排放。材料内部构筑起宏孔-微孔三维多级孔道结构,可提供大量活性位点用于金属离子固载,促使Cu²⁺均匀分布在多级孔隙体系内,进而实现理想的离子缓释效果。分散均匀的铜离子使陶瓷具备优异的抗菌性能,同时铜源原材料成本低廉。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122997122A_ABST
    Figure CN122997122A_ABST
Patent Text Reader

Abstract

The application provides a method for preparing a nano copper / SiC composite antibacterial material with a three-dimensional pore structure by confined freezing, and the method uses SiC and Al2O3 as main raw materials, deionized water as a solvent, PVA as a binder, CMC as a suspending agent, and glycerol as a defoaming agent. The PVA and CMC are dissolved by heating and stirring, then the glycerol is added, and then the pH value is adjusted by using ammonia water to prepare a mixed solution. Then, the SiC powder and the Al2O3 powder are added and mixed on a planetary ball mill to form a mixed slurry. Then, the mixed slurry is subjected to confined freezing, the cooling direction of the slurry is controlled, and thus a solid body with certain macroscopic pores is obtained. The drying treatment is carried out under a low pressure condition, at this time, the sublimation of ice occurs to generate pores. Then, the obtained green body is sintered. Finally, the functional ion Cu 2+ is loaded onto the porous carrier, i.e. the surface of the porous ceramic, by a vacuum adsorption method. The nano copper / SiC composite antibacterial material prepared by the method has excellent pore structure and antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous ceramic materials technology, specifically to a method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing. Background Technology

[0002] Porous ceramics are inorganic non-metallic materials containing numerous pores. They utilize the structure and surface area of ​​these pores, combined with the material's inherent properties, to achieve desired physical and chemical properties such as thermal, electrical, magnetic, and optical properties. Therefore, they can be used for applications including filtration, separation, dispersion, permeation, heat insulation, heat exchange, sound absorption, sound insulation, adsorption, carriers, reactions, sensing, and biological applications. In recent years, porous ceramics have attracted significant attention in the fields of functional carriers and antibacterial materials due to their unique advantages such as controllable pore structure, large specific surface area, and excellent pore connectivity.

[0003] Compared to dense ceramics, porous ceramics can provide abundant surface adsorption sites and loading space, which can effectively achieve uniform anchoring and stable immobilization of metal ions, and significantly improve the problems of active ions being easy to aggregate and lose.

[0004] Therefore, improving the porous structure of porous ceramics to increase the contact area between the material and bacteria, thereby enhancing the sustained release efficiency of active ions and the interfacial antibacterial effect, demonstrates significant application advantages and research value in the field of long-lasting, stable, and broad-spectrum antibacterial functional ceramic materials. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a three-dimensional porous copper / SiC composite antibacterial material by confined freezing. The method involves preparing porous silicon carbide ceramic by freeze drying, and then loading copper ions onto the prepared porous silicon carbide ceramic by vacuum adsorption to prepare the antibacterial ceramic.

[0006] This invention provides a method for confined cryogenic preparation of a three-dimensional porous nano-copper / SiC composite antibacterial material, comprising the following steps:

[0007] (1) Grinding and mixing: Weigh SiC powder, Al2O3 powder, PVA and CMC according to a certain ratio. First, add PVA and CMC to deionized water and heat to 80°C with a magnetic heating stirrer while stirring. Then stop heating and continue stirring until dissolved. Next, add a certain amount of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls according to a certain ball-to-material ratio. Put SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar. Place it on a planetary ball mill and mix for a certain time. Filter to remove grinding balls to obtain a mixed slurry.

[0008] (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a mold made of polyvinyl chloride. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -35~37℃ for 10~14 hours to allow the ice crystals to grow completely and obtain crystals.

[0009] (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -50~60℃ for 10~14h, and then demolded to obtain the green body;

[0010] (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200℃ and sintered for 2 hours to obtain porous silicon carbide ceramic.

[0011] (5) Vacuum impregnation: Weigh copper nitrate trihydrate and dissolve it in the dark to obtain a copper nitrate solution with a concentration of 0.1~0.4mol / L. Pour the copper nitrate solution into a vacuum adsorption container and then put the porous silicon carbide ceramic prepared in step (4) into the vacuum adsorption container so that the porous silicon carbide ceramic is immersed in the copper nitrate solution. Start the circulating water multi-purpose vacuum pump to vacuum the adsorption container and evacuate it. The porous silicon carbide ceramic is impregnated under vacuum conditions for 2 hours. Repeat the above impregnation operation several times, and then take it out and dry it to obtain the adsorption ceramic sample.

[0012] (6) Secondary sintering: The adsorption ceramic sample obtained in step (5) is placed in a muffle furnace, heated to 400℃ and sintered for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

[0013] Preferably, in step (1), the solid content of the mixed slurry is 30 vol%, wherein the mass ratio of SiC powder to Al2O3 powder is 9:1, the amount of PVA is 1 wt% of the mass of SiC powder, the amount of CMC is 0.1 wt% of the mass of SiC powder, and the amount of glycerol is 1 vol% of the volume of deionized water.

[0014] Preferably, the magnetic heating stirrer in step (1) rotates at 1200 rpm.

[0015] Preferably, in step (1), the mass ratio of grinding balls to the mixture is 1.5:1, the planetary ball mill speed is 400 rpm, and the mixing time is 2~3 h.

[0016] Preferably, in step (2), the inner diameter of the mold is 10~20mm, the freezing temperature in the refrigerator is -36℃, and the freezing time is 12h.

[0017] Preferably, the freeze-drying temperature of the freeze dryer in step (3) is -55°C.

[0018] Preferably, the heating rate of the muffle furnace in steps (4) and (6) is 10°C / min, and the furnace is cooled after the heat preservation sintering is completed.

[0019] Preferably, the vacuum impregnation in step (5) is performed 6 times, and the vacuum degree of the circulating water multi-purpose vacuum pump is 0.08±0.02MPa.

[0020] Preferably, the drying temperature in step (5) is 70~80℃ and the drying time is 2~3h.

[0021] Preferably, the filtration container in step (5) is a filtration flask.

[0022] The preparation principle of this invention: The method for preparing nano-copper / SiC composite antibacterial materials with a three-dimensional porous structure by confined freezing of the present invention uses SiC powder and Al2O3 powder as the main raw materials, deionized water as the solvent, PVA (polyvinyl alcohol) as the binder, CMC (sodium carboxymethyl cellulose) as the suspending agent, and glycerol as the defoamer. First, PVA and CMC are dissolved by heating and stirring, then glycerol is added and mixed. The pH is then adjusted to 11 using ammonia water. Next, SiC powder and Al2O3 powder are added, and the mixture is stirred in a planetary ball mill to form a uniformly dispersed slurry. Then, the slurry is subjected to confined freezing. By controlling the cooling direction of the slurry, a solid with a certain macroscopic pore size of 200-300 μm is obtained. Subsequently, drying is performed under low-pressure conditions, during which ice sublimation occurs, generating macropores and mesopores. The resulting green body is then sintered. During sintering, the pores left by ice sublimation are preserved, and the solvent water is converted into gas, forming mesopores and micropores with a pore size of <50 nm. The porous material prepared through the above process has macroscopically arranged oriented openings, and mesopores and micropores are contained in the walls of adjacent openings. Finally, ions are loaded using vacuum adsorption to add functional Cu ions. 2+ Through the adsorption-diffusion mechanism under vacuum, the material is uniformly and efficiently loaded onto the porous carrier, i.e., the porous ceramic surface.

[0023] This invention utilizes a freeze-drying process to prepare porous ceramics, resulting in samples with regular pore sizes and high specific surface areas. This preparation process is environmentally friendly, with no harmful substances emitted throughout. The material's internal structure forms a three-dimensional hierarchical pore system of macropores and micropores, providing numerous active sites for metal ion immobilization and promoting the uniform distribution of Cu²⁺ within the hierarchical pore system, thereby achieving an ideal ion-releasing effect. The uniformly dispersed copper ions endow the ceramics with excellent antibacterial properties, while the copper source raw material is inexpensive.

[0024] This invention utilizes loaded nano-copper to generate antibacterial capabilities. Nano-copper, due to its small particle size and large specific surface area, disrupts bacterial structure through the dual effects of releasing copper ions and generating reactive oxygen species, resulting in an antibacterial effect far superior to micron-sized copper. Compared to nano-silver, copper is an essential element for the human body, exhibits better biocompatibility, and is less likely to induce antibiotic resistance in bacteria; moreover, copper raw materials are abundant, reducing preparation costs. Nano-copper possesses excellent high-temperature resistance, making it suitable for the high-temperature preparation environment of ceramics. A relatively low addition amount can achieve a broad-spectrum and long-lasting antibacterial effect, while also exhibiting thermal and electrical conductivity. Although elemental nano-copper is prone to oxidation, this problem can be mitigated through coating modification. Therefore, nano-copper has significant application value as an inorganic antibacterial agent.

[0025] This invention employs a vacuum adsorption method for copper ion loading, utilizing a negative pressure environment to eliminate air resistance within the carrier pores. This allows solutions or gases containing target ions to rapidly and uniformly penetrate into the micropores, mesopores, and even nanopores of the carrier. The vacuum environment eliminates the "air clogging" effect within the pores, enabling the ion solution to penetrate to the deepest parts of the carrier, avoiding the "surface enrichment, internal voids" problem common in traditional impregnation methods. The negative pressure difference accelerates the mass transfer process, significantly shortening the loading time. Under vacuum conditions, the solution volume can be reduced by 30%-50%, lowering wastewater treatment costs. It exhibits excellent permeability to micropores (<2nm), mesopores (2-50nm), and even nanopores, making it particularly suitable for carriers such as molecular sieves and porous ceramics.

[0026] The beneficial effects of this invention are as follows: The method for preparing nano-copper / SiC composite antibacterial materials with a three-dimensional porous structure using confined freezing involves preparing porous silicon carbide via confined freezing and then loading copper ions using vacuum adsorption to obtain antibacterial ceramics. Firstly, the porous silicon carbide ceramic with a three-dimensional porous structure prepared by the confined freezing method has a large specific surface area, regular and controllable pore size, and a multi-level pore structure including macropores, mesopores, and micropores, providing abundant loading sites. Secondly, when loading copper ions using vacuum adsorption, the copper ion loading rate of the ceramic material is greatly enhanced, with copper ions uniformly distributed in each level of the pores, resulting in a significant ion slow-release effect. The excellent antibacterial properties imparted by copper ions are thus greatly improved. Furthermore, this invention uses a confined freezing method to prepare nano-copper / SiC composite antibacterial materials, employing low-cost copper source materials, a green and pollution-free preparation process, and a simple preparation procedure, resulting in significant comprehensive advantages. Attached Figure Description

[0027] Figure 1 XRD patterns of the nano-copper / SiC composite materials prepared according to Examples 1 to 4.

[0028] Figure 2 This is a cross-sectional view of the nano-copper / SiC composite material prepared according to Example 4.

[0029] Figure 3 EDS diagram of the nano-copper / SiC composite material prepared according to Example 4.

[0030] Figure 4 The copper loading rate curves are shown for the nano-copper / SiC composite materials prepared according to Examples 1 to 4.

[0031] Figure 5 The results show the antibacterial test results of the nano-copper / SiC composite materials prepared according to Example 4 and Comparative Example 1. Detailed Implementation

[0032] To make the technical solution of the present invention easier to understand, the technical solution of the present invention will now be clearly and completely described in conjunction with the accompanying drawings and specific embodiments.

[0033] Example 1:

[0034] The method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing in this embodiment includes the following steps:

[0035] (1) Grinding and mixing: Weigh 17.5284g of SiC powder, 1.9476g of Al2O3 powder, 0.17g of PVA and 1.7g of CMC. First, add PVA and CMC to 14mL of deionized water. Heat to 80℃ using a magnetic stirrer at 1200rpm. Then stop heating and continue stirring until dissolved. Next, add 0.14mL of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls at a ball-to-powder mass ratio of 1.5:1. Put SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar and place it on a planetary ball mill. Mix at 400rpm for 2 hours. Filter to remove grinding balls to obtain a mixed slurry.

[0036] (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a polyvinyl chloride mold with a diameter of 10 mm. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -35℃ for 10 hours to allow the ice crystals to grow completely and obtain crystals.

[0037] (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -50℃ for 10 hours. Then, the crystals are demolded to obtain the green blank.

[0038] (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200°C at a rate of 10°C / min and held for 2 hours to obtain porous silicon carbide ceramic.

[0039] (5) Vacuum impregnation: Weigh copper nitrate trihydrate and dissolve it in the dark to obtain a copper nitrate solution with a concentration of 0.1 mol / L. Pour the copper nitrate solution into a vacuum adsorption container and then put the porous silicon carbide ceramic prepared in step (4) into a vacuum filtration flask so that the porous silicon carbide ceramic is immersed in the copper nitrate solution. Start the circulating water multi-purpose vacuum pump to evacuate the vacuum filtration flask. The porous silicon carbide ceramic is impregnated under a vacuum of 0.08 MPa for 2 hours. Repeat the above impregnation operation 6 times. Then take it out and dry it at 70°C for 2 hours to obtain the adsorption ceramic sample.

[0040] (6) Secondary sintering: The adsorption ceramic sample obtained in step (5) is placed in a muffle furnace, heated to 400°C at a rate of 10°C / min and held for sintering for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

[0041] Example 2:

[0042] The method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing in this embodiment includes the following steps:

[0043] (1) Grinding and mixing: Weigh 17.5284g of SiC powder, 1.9476g of Al2O3 powder, 0.17g of PVA and 1.7g of CMC. First, add PVA and CMC to 14mL of deionized water. Heat to 80℃ using a magnetic stirrer at 1200rpm. Then stop heating and continue stirring until dissolved. Next, add 0.14mL of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls at a ball-to-powder mass ratio of 1.5:1. Put SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar and place it on a planetary ball mill. Mix at 400rpm for 2.5h. Filter to remove grinding balls to obtain a mixed slurry.

[0044] (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a PVC mold with a diameter of 10 mm. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -35℃ for 12 hours to allow the ice crystals to grow completely and obtain crystals.

[0045] (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -55℃ for 12 hours. Then, the crystals are demolded to obtain the green blank.

[0046] (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200°C at a rate of 10°C / min and held for 2 hours to obtain porous silicon carbide ceramic.

[0047] (5) Vacuum impregnation: Weigh copper nitrate trihydrate and dissolve it in the dark to obtain a copper nitrate solution with a concentration of 0.2 mol / L. Pour the copper nitrate solution into a vacuum adsorption container and then put the porous silicon carbide ceramic prepared in step (4) into a vacuum filtration flask so that the porous silicon carbide ceramic is immersed in the copper nitrate solution. Start the circulating water multi-purpose vacuum pump to evacuate the vacuum filtration flask. The porous silicon carbide ceramic is impregnated under a vacuum of 0.08 MPa for 2 hours. Repeat the above impregnation operation 6 times. Then take it out and dry it at 75°C for 2 hours to obtain the adsorption ceramic sample.

[0048] (6) Secondary sintering: The adsorption ceramic sample obtained in step (5) is placed in a muffle furnace, heated to 400°C at a rate of 10°C / min and held for sintering for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

[0049] Example 3:

[0050] The method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing in this embodiment includes the following steps:

[0051] (1) Grinding and mixing: Weigh 17.5284g of SiC powder, 1.9476g of Al2O3 powder, 0.17g of PVA and 1.7g of CMC. First, add PVA and CMC to 14mL of deionized water. Heat to 80℃ using a magnetic stirrer at 1200rpm. Then stop heating and continue stirring until dissolved. Next, add 0.14mL of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls at a ball-to-powder mass ratio of 1.5:1. Put the SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar and place it on a planetary ball mill. Mix at 400rpm for 3 hours. Filter to remove the grinding balls to obtain a mixed slurry.

[0052] (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a polyvinyl chloride mold with a diameter of 10 mm. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -37℃ for 14 hours to allow the ice crystals to grow completely and obtain crystals.

[0053] (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -60℃ for 14 hours. Then, the crystals are demolded to obtain the green blank.

[0054] (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200°C at a rate of 10°C / min and held for 2 hours to obtain porous silicon carbide ceramic.

[0055] (5) Vacuum impregnation: Weigh copper nitrate trihydrate and dissolve it in the dark to obtain a copper nitrate solution with a concentration of 0.3 mol / L. Pour the copper nitrate solution into a vacuum adsorption container and then put the porous silicon carbide ceramic prepared in step (4) into a vacuum filtration flask so that the porous silicon carbide ceramic is immersed in the copper nitrate solution. Start the circulating water multi-purpose vacuum pump to evacuate the vacuum filtration flask. The porous silicon carbide ceramic is impregnated under a vacuum of 0.08 MPa for 2 hours. Repeat the above impregnation operation 6 times. Then take it out and dry it at 80°C for 2 hours to obtain the adsorption ceramic sample.

[0056] (6) Secondary sintering: The adsorption ceramic sample obtained in step (5) is placed in a muffle furnace, heated to 400°C at a rate of 10°C / min and held for sintering for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

[0057] Example 4:

[0058] The method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing in this embodiment includes the following steps:

[0059] (1) Grinding and mixing: Weigh 17.5284g of SiC powder, 1.9476g of Al2O3 powder, 0.17g of PVA and 1.7g of CMC. First, add PVA and CMC to 14mL of deionized water. Heat to 80℃ using a magnetic stirrer at 1200rpm. Then stop heating and continue stirring until dissolved. Next, add 0.14mL of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls at a ball-to-powder mass ratio of 1.5:1. Put SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar and place it on a planetary ball mill. Mix at 400rpm for 2 hours. Filter to remove grinding balls to obtain a mixed slurry.

[0060] (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a PVC mold with a diameter of 10 mm. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -35℃ for 12 hours to allow the ice crystals to grow completely and obtain crystals.

[0061] (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -55℃ for 12 hours. Then, the crystals are demolded to obtain the green blank.

[0062] (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200°C at a rate of 10°C / min and held for 2 hours to obtain porous silicon carbide ceramic.

[0063] (5) Vacuum impregnation: Weigh copper nitrate trihydrate and dissolve it in the dark to obtain a copper nitrate solution with a concentration of 0.4 mol / L. Pour the copper nitrate solution into a vacuum adsorption container and then put the porous silicon carbide ceramic prepared in step (4) into a vacuum filtration flask so that the porous silicon carbide ceramic is immersed in the copper nitrate solution. Start the circulating water multi-purpose vacuum pump to evacuate the vacuum filtration flask. The porous silicon carbide ceramic is impregnated under a vacuum of 0.08 MPa for 2 hours. Repeat the above impregnation operation 6 times. Then take it out and dry it at 75°C for 2 hours to obtain the adsorption ceramic sample.

[0064] (6) Secondary sintering: The adsorption ceramic sample obtained in step (5) is placed in a muffle furnace, heated to 400°C at a rate of 10°C / min and held for sintering for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

[0065] Comparative Example 1:

[0066] The method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing in this embodiment includes the following steps:

[0067] (1) Grinding and mixing: Weigh 17.5284g of SiC powder, 1.9476g of Al2O3 powder, 0.17g of PVA and 1.7g of CMC. First, add PVA and CMC to 14mL of deionized water. Heat to 80℃ using a magnetic stirrer at 1200rpm. Then stop heating and continue stirring until dissolved. Next, add 0.14mL of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls at a ball-to-powder mass ratio of 1.5:1. Put SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar and place it on a planetary ball mill. Mix at 400rpm for 2 hours. Filter to remove grinding balls to obtain a mixed slurry.

[0068] (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a PVC mold with a diameter of 10 mm. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -35℃ for 12 hours to allow the ice crystals to grow completely and obtain crystals.

[0069] (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -55℃ for 12 hours. Then, the crystals are demolded to obtain the green blank.

[0070] (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200°C at a rate of 10°C / min and held for 2 hours to obtain porous silicon carbide ceramic.

[0071] (5) Secondary sintering: The porous silicon carbide ceramic sample obtained in step (4) is placed in a muffle furnace, heated to 400°C at a rate of 10°C / min and held for sintering for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

[0072] II. Performance Testing

[0073] The phase composition of the ceramics prepared in Examples 1 to 4 and Comparative Example 1 was analyzed using an X-ray diffractometer (XRD, Shimadzu-6000, Japan), the microstructure of the ceramics was analyzed using a Japanese TM4000 desktop scanning electron microscope, the types and distribution of ceramic elements were analyzed using a thermal field emission scanning electron microscope, and the loading rate was calculated by measuring the sample weight gain using a precision electronic balance.

[0074] Figure 1 XRD patterns of the nano-copper / SiC composite materials prepared according to Examples 1 to 4. Figure 1 It can be seen that after vacuum impregnation with CuNO3 solutions of different concentrations, Cu elements adhere to the porous silicon carbide ceramics, proving that the vacuum impregnation method has a good ability to allow ions to enter the pores of porous silicon carbide ceramics.

[0075] Figure 2 This is a cross-sectional view of the nano-copper / SiC composite material prepared according to Example 4. Figure 2 It can be seen that porous silicon carbide ceramics have excellent pore structure, which can provide more attachment sites for Cu ions.

[0076] Figure 3 EDS image of the nano-copper / SiC composite material prepared according to Example 4. Figure 3 It can be seen that Cu ions are attached to the inner wall of the pores and are distributed relatively evenly.

[0077] Figure 4 The copper loading rate curves are shown for the nano-copper / SiC composite materials prepared according to Examples 1 to 4. Figure 4 It can be seen that as the number of impregnations increases, the loading rate of Cu ions decreases; the higher the concentration of CuNO3, the higher the loading rate.

[0078] Figure 5The results show the antibacterial test results of the nano-copper / SiC composite materials prepared according to Example 4 and Comparative Example 1. Figure 5 It can be seen that the number of surviving Escherichia coli in the petri dish decreases with the increase of CuNO3 solution concentration in the vacuum impregnation of porous silicon carbide ceramics.

[0079] Table 1 shows the antibacterial test results of the nano-copper / SiC composite materials prepared according to Example 4 and Comparative Example 1. As can be seen from Table 1, the bactericidal rate gradually increases with the increase of CuNO3 concentration, reaching a maximum of 99.99% at 0.4 mol / L.

[0080] Table 1. Sterilization rate of nano-copper / SiC composite materials prepared by impregnation with different CuNO3 concentrations

[0081] Comparative Example 1 <![CDATA[2.6×10 5 ]]> / Example 1 - 0.10 mol / L <![CDATA[1.34×10 4 ]]> 94.85 Example 2 - 0.20 mol / L <![CDATA[4.6×10 3 ]]> 98.23 Example 3 - 0.30 mol / L <![CDATA[2.6×10 2 ]]> 99.90 Example 4 - 0.40 mol / L <![CDATA[3×10 1 ]]> 99.99

[0082] It should be noted that the embodiments described herein are only some embodiments of the present invention, and not all implementations of the present invention. These embodiments are merely illustrative and are intended only to provide a more intuitive and clear way to understand the content of the present invention, not to limit the technical solutions described herein. All other implementation methods that can be conceived by those skilled in the art without creative effort, as well as other simple substitutions and variations of the technical solutions of the present invention, without departing from the concept of the present invention, are within the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional porous nano-copper / SiC composite antibacterial material by confined freezing, characterized in that, Includes the following steps: (1) Grinding and mixing: Weigh SiC powder, Al2O3 powder, PVA and CMC according to a certain ratio. First, add PVA and CMC to deionized water and heat to 80°C with a magnetic heating stirrer while stirring. Then stop heating and continue stirring until dissolved. Next, add a certain amount of glycerol and then add ammonia to adjust the pH to 11±0.5 to obtain a mixture. Weigh grinding balls according to a certain ball-to-material ratio. Put SiC powder, Al2O3 powder, mixture and grinding balls into a grinding jar. Place it on a planetary ball mill and mix for a certain time. Filter to remove grinding balls to obtain a mixed slurry. (2) Freeze-crystallization: The mixed slurry obtained in step (1) is injected into a mold made of polyvinyl chloride. Then the mold is placed on a copper block in a heat-insulating barrel. Liquid nitrogen is poured into the bottom of the heat-insulating barrel, the lid of the heat-insulating barrel is closed, and the frozen material is taken out after heat preservation for 5 minutes. Then it is placed in a refrigerator and frozen at -35~37℃ for 10~14 hours to allow the ice crystals to grow completely and obtain crystals. (3) Crystal freeze-drying: The crystals obtained in step (2) are placed in a freeze dryer and freeze-dried at -50~60℃ for 10~14h, and then demolded to obtain the green body; (4) Sintering of green body: The green body obtained in step (3) is placed in a muffle furnace, heated to 1200℃ and sintered for 2 hours to obtain porous silicon carbide ceramic. (5) Vacuum impregnation: Weigh copper nitrate trihydrate and dissolve it in the dark to obtain a copper nitrate solution with a concentration of 0.1~0.4mol / L. Pour the copper nitrate solution into a vacuum adsorption container and then put the porous silicon carbide ceramic prepared in step (4) into the vacuum adsorption container so that the porous silicon carbide ceramic is immersed in the copper nitrate solution. Start the circulating water multi-purpose vacuum pump to vacuum the adsorption container and evacuate it. The porous silicon carbide ceramic is impregnated under vacuum conditions for 2 hours. Repeat the above impregnation operation several times, and then take it out and dry it to obtain the adsorption ceramic sample. (6) Secondary sintering: The adsorption ceramic sample obtained in step (5) is placed in a muffle furnace, heated to 400℃ and sintered for 2 hours to obtain porous silicon carbide ceramic containing copper ions.

2. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, In step (1), the solid content of the mixed slurry is 30 vol%, wherein the mass ratio of SiC powder to Al2O3 powder is 9:1, the amount of PVA is 1 wt% of the mass of SiC powder, the amount of CMC is 0.1 wt% of the mass of SiC powder, and the amount of glycerol is 1 vol% of the volume of deionized water.

3. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, In step (1), the magnetic heating stirrer rotates at 1200 rpm.

4. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, In step (1), the mass ratio of grinding balls to the mixture is 1.5:1, the planetary ball mill speed is 400 rpm, and the mixing time is 2~3 h.

5. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, In step (2), the inner diameter of the mold is 10~20mm, the freezing temperature in the refrigerator is -36℃, and the freezing time is 12h.

6. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, The freeze-drying temperature of the freeze dryer in step (3) is -55℃.

7. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, The heating rate of the muffle furnace in steps (4) and (6) is 10℃ / min, and the furnace is cooled after the heat preservation sintering is completed.

8. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, The vacuum impregnation process in step (5) is repeated 6 times, and the vacuum degree of the circulating water multi-purpose vacuum pump is 0.08±0.02MPa.

9. The method for preparing three-dimensional porous nano-copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, In step (5), the drying temperature is 70~80℃ and the drying time is 2~3h.

10. The method for preparing three-dimensional porous copper / SiC composite antibacterial materials by confined freezing as described in claim 1, characterized in that, In step (5), the filtration container is a filtration flask.